Natural occurrence of the diamond hexagonal structure in silicon nanowires grown by a plasma-assisted vapour–liquid–solid method. Issue 24 (12th June 2017) - Tang, J.; Maurice, J.-L.; Fossard, F.; Florea, I.; Chen, W.; Johnson, E. V.; Foldyna, M.; Yu, L.; Roca i Cabarrocas, P.
Abstract : Diamond-hexagonal silicon demonstrated in as-grown vapour–liquid–solid nanowires. Abstract : Silicon nanowires have been grown by a plasma-assisted vapour–liquid–solid method using tin as the catalyst. Transmission electron microscopy in the [12̄10] zone axis shows that the diamond hexagonal ( P 63 / mmc ) crystal structure is present in several nanowires. This is the first unambiguous proof of the natural occurrence of this metastable phase to our knowledge.